Blunted Post-COVID-19 Humoral Immunity in Patients With CNS Demyelinating Disorders on Anti-CD20 Treatments - Money, Kelli M.; Baber, Ursela; Saart, Emma; Samaan, Soleil; Sloane, Jacob A. (Frontiers in Neurology, 2022)
With unclear characteristics of post-infection and post-vaccination immunity, the multiple sclerosis community lacks evidence to guide patients on their continued coronavirus disease 2019 (COVID-19) infection risk. As disease modifying treatments all modulate the immune system, we expect their use to alter acquired immunity to COVID-19, but the specific impact of individual treatments is unclear. To address this, we analyzed the patient and COVID-19 specific characteristics associated with post-infection humoral immunity in 58 patients with central nervous system (CNS) demyelinating disorders in the Boston metropolitan area. Univariate analysis of variance was performed using Mann Whitney U test for continuous variables, and Chi Square or Fisher Exact test for nominal variables. Univariate and stepwise multivariate nominal logistic regression identified clinical characteristics associated with COVID-19 specific nucleocapsid IgG antibody formation post-infection. Our cohort demonstrated a 42% post-infection seropositive rate with a significantly higher rate observed with shorter duration between infection and antibody collection and use of natalizumab over no/other treatment. Use of anti-CD20 treatments compared to no/other treatment was associated with a significantly lower rate of seropositivity. However, only shorter duration between infection and antibody collection as well as use of no/other treatment compared to anti-CD20 treatment were found to be independently associated with increased likelihood of post-infection seropositivity. Additionally, we demonstrate durability of antibody response up to 9 months in a small subset of patients. Thus, our data supports that patients with CNS demyelinating disorders regardless of DMT are able to form a measurable antibody response after COVID-19 infection, and that patients on anti-CD20 treatments form less robust immunity after COVID-19 infection.